Additive manufacturing of bulk metallic glass: Principles, materials and prospects - Wenzheng Wu; Xuechao Li; Qingping Liu; Jerry Ying Hsi Fuh; Aodu Zheng; Yiming Zhou; Luquan Ren; Guiwei Li (Materials Today Advances, 2022)
Additive manufacturing of metallic glass has attracted great attentions from researchers owing to the prospect of free-form fabricating high-performance bulk amorphous alloy parts. The characteristics of additive manufacturing from points to tracks, tracks to layers, and layers to parts are suitable for forming complex bulk metallic glass parts, which are difficult to achieve with other processing technologies. Herein, the forming principles used in metallic glass additive manufacturing are reviewed, with an emphasis on the manufacturing processes, material systems, forming part properties and potential applications. The properties of forming bulk metallic glass via selective laser melting, laser-directed energy deposition, and laser foil printing technologies are summarized. In addition, certain newly explored metallic glass additive manufacturing technologies, such as fused filament fabrication, ultrasonic consolidation, thermal spraying, and pneumatic injection, are briefly introduced. Finally, the trends in metallic glass additive manufacturing and perspectives for this emerging field are discussed.